Modernização da carreira de profissionais da saúde : cartilha de orientação - Primo, Paola Pinheiro Bernardi (2014)
Public administration has been undergoing big changes in the past years. Imported management administration concepts reflect in the way the State is managed. In the management of people, focus on the citizen and in the efficacy of services delivered is being demanded through policies aimed at the management for the public servant’s competence and better development. Specially in the area of Healthcare, the demand for better quality of life on the job, and to lessen the precariousness at the job have culminated in the publication of guidelines for the creation of career plans for the public servants. This work has as its main aim the elaboration of a guidebook to provide the public administrators with important parameters and concepts to be considered when designing career plans for public servants in the area of healthcare. The laws that deal with the institution of the Public Management Program, the career plans of federal public servants, and the bill that established the guidelines for the creation of career plans for healthcare public servants were used as data. The environment of the study was an Extension program at the Universidade Federal do Espírito Santo, which works using the concept of modernization for public administration, mainly helping municipalities to implement new management concepts, including the re-formulation or the creation of career plans. The results found allow the assertion that, although the legislation points to the effective modernization of the public administration regarding the design of career plans, this process is still incipient in the municipalities, and the creation of instruments to guide public administrators will have great value, both to the public administration as for society